American Heart Association and the Pharmaceutical Roundtable - Adler, Stephen M.; Leighton, Hallie (Henry Stewart Talks, 2017)
The case study reviews how the American Heart Association harnessed the collective power of several pharmaceutical companies to promote cardiovascular health messages across the US.